History In The Classroom: The Transformation of The History Curriculum In Indonesia: Sejarah dalam Ruang Kelas: Transformasi Kurikulum Sejarah di Indonesia - Muhammad Junaldi Jufri; M. Budiman Budiman; Juan Fahirza Putra Putra (Jurnal Pendidikan Sejarah, 2026)
This article discusses the dynamics of changes in the history curriculum at the senior high school (SMA) level during three periods of Indonesian government: Old Order, New Order, and Reformation. This study uses a library research method by reviewing curriculum documents, textbooks, and relevant academic literature. The results show that changes in the history curriculum cannot be separated from the ideological and political interests of each ruling regime. During the Old Order era, the curriculum focused on the formation of post- independence national identity. In the New Order era, history was used as a tool for legitimizing power and systematically instilling state ideology through a centralized curriculum. Meanwhile, the Reformation era brought the spirit of decentralization, critical approaches, and strengthening historical thinking competencies. Through this analysis, it can be seen that the transformation of the history curriculum reflects the changing orientation of the state in shaping the character and historical awareness of the younger generation.